2014
DOI: 10.1186/s12931-014-0118-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different mesenchymal stromal cell sources and delivery routes in experimental emphysema

Abstract: We sought to assess whether the effects of mesenchymal stromal cells (MSC) on lung inflammation and remodeling in experimental emphysema would differ according to MSC source and administration route. Emphysema was induced in C57BL/6 mice by intratracheal (IT) administration of porcine pancreatic elastase (0.1 UI) weekly for 1 month. After the last elastase instillation, saline or MSCs (1×105), isolated from either mouse bone marrow (BM), adipose tissue (AD) or lung tissue (L), were administered intravenously (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
193
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(207 citation statements)
references
References 53 publications
12
193
2
Order By: Relevance
“…In the study of Antunes et al [30], injection of L-MSCs via the right jugular vein led to the death of all injected mice, which was not observed after intravenous administration of either A-MSCs or BM-MSCs in this study. In contrast, intravenous injection of L-MSCs into the tail vein, as demonstrated by Hoffman et al [25], did not lead to lethality.…”
Section: Msc Treatment In Preclinical Models Of Emphysemasupporting
confidence: 40%
See 2 more Smart Citations
“…In the study of Antunes et al [30], injection of L-MSCs via the right jugular vein led to the death of all injected mice, which was not observed after intravenous administration of either A-MSCs or BM-MSCs in this study. In contrast, intravenous injection of L-MSCs into the tail vein, as demonstrated by Hoffman et al [25], did not lead to lethality.…”
Section: Msc Treatment In Preclinical Models Of Emphysemasupporting
confidence: 40%
“…Only BM-MSCs displayed beneficial systemic effects, while A-MSCs and L-MSCs showed a more significant reduction in the fractional area of alveolar collapse than BM-MSCs [30]. Another study compared human L-MSCs and BM-MSCs in vitro and observed that L-MSCs expressed higher levels of the stemness-related marker nestin, which may have consequences for their ability to differentiate into different cell types [31].…”
Section: Msc Treatment In Preclinical Models Of Emphysemamentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, animals received either HLFs ( n = 6), mMSCs ( n = 6), BMDMCs ( n = 13), or BMDMCs depleted of either CD45 ( n = 6), CD34 ( n = 6), CD3 ( n = 6), CD19 ( n = 6), CD11b ( n = 9), CD31 ( n = 6), or Sca-1 ( n = 6) cells (Fig. 1B) [16, 19, 20, 24, 25, 35, 36]. …”
Section: Methodsmentioning
confidence: 99%
“…from different sources were compared, even when cells have similar proliferation and differentiation capacities (9). As an example, BM derived-MSCs are able to inhibit the release of pro-inflammatory cytokines and stimulate the functional activity of regulatory T-lymphocytes (10,11).…”
Section: Francesca Polverinomentioning
confidence: 99%